(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
In today’s fast-paced life, ensuring food’s freshness, safety, and optimal nutritional and economic value is paramount for both consumers and businesses. Textiles have played a significant role in the food preservation industry throughout history. With the continuous development of the textile and preservation industries, novel methods have been explored to enhance the effectiveness of preservation. This article provides a comprehensive overview of textiles’ performance requirements and limitations in the food preservation process. Additionally, it introduces innovative techniques and recent advancements in textile materials designed explicitly for preservation purposes. Furthermore, the paper highlights the key challenges that must be addressed in future research. Consequently, this scientific review serves as a valuable reference for the application and advancement of textiles in the dynamic field of food preservation.